Lifeline rate and senior citizen discount on electricity: Who pays and who benefits? (socialized pricing mechanisms in the Philippine electric power industry) - Kris A. Francisco (Philippine Institute for Development Studies (PIDS), 2024)
Socialized pricing mechanisms are common in utility services like electricity because it is critical for daily activities and therefore, considered vital for economic growth. The aim of such mechanisms is to redistribute financial resources from well-off to marginalized consumers. This is seen to improve the availability and affordability of critical services, thus enhancing the overall social welfare. However, while the rationale for socialized pricing mechanisms is widely accepted, funding-related discussions have induced much debate. Some studies found that subsidies for electricity end up benefiting middle-income and high-income households instead of the poor, exposing possible targeting issues (Mayer et al. 2015, Trimble at al. 2011, Komives et al 2009). Motivated by these discussions, this study examines two presently implemented socialized pricing mechanisms in the Philippine Electric Power Industry namely: (1) the lifeline rate, and (2) the senior citizen rate. The analysis employed data from the Household Energy Consumption Survey and Family Income and Expenditure Survey from which it was shown that the set of rules for availing the discounts is prone to leakages, favoring electricity consumers that can well afford to pay their electricity consumption at full price. Some recommendations on addressing implementation issues are presented in this paper.
Keywords: 330; utility services; electricity; socialized pricing; Philippine Electric Power Industry